Iron metabolism in patients with Graves' hyperthyroidism. (14th September 2017) - Fischli, Stefan; von Wyl, Viktor; Trummler, Michael; Konrad, Daniel; Wueest, Stephan; Ruefer, Axel; Heering, Kerstin; Streuli, Regina; Steuer, Christian; Bernasconi, Luca; Recher, Mike; Henzen, Christoph
Summary: Objectives: Graves' hyperthyroidism (GH) interferes with iron metabolism and elevates ferritin. The precise mechanisms remain unclear. The influence of thyroid hormones on the synthesis/regulation of hepcidin, an important regulator of iron metabolism, remains uncharacterized. Design: Prospective observational study. Patients: We included patients (n = 31) with new‐onset and untreated GH. Measurements: Laboratory parameters indicative of iron metabolism (ferritin, transferrin, hepcidin), inflammatory markers/cytokines and smoking status were assessed at the diagnosis of GH (T0) and at euthyroidism (T1) in the same patients using multivariable analyses. Hepcidin was measured by mass spectrometry (hepcidinMS ) and ELISA (hepcidinEL ). The impact of T3 on hepatic hepcidin expression was studied in a cell culture model using HepG2 cells. Results: Median ferritin levels were significantly lower and transferrin significantly higher at T1 than at T0. HepcidinMS levels were lower in males and females at T1 (statistically significant in males only). No statistically significant difference in hepcidinEL was detected between T0 and T1. Plasma levels of inflammatory markers (high‐sensitive CRP, procalcitonin) and cytokines (interleukin 6, interleukin 1ß, tumour necrosis factor α) were not different between T0 and T1. Smokers tended to have lower fT3 and fT4 at T0 than nonsmoking GH patients. T3 significantly induced hepcidin mRNA expression in HepG2 cells. Conclusions: Iron metabolism in patients with GH undergoes dynamic changes in patients with GH that resemble an acute‐phase reaction. Inflammatory parameters and cytokines were unaffected by thyroid status. Gender and smoking status had an impact on ferritin, hepcidin and thyroid hormones.